Essential components of health assessment for older people in primary care: a cross‐sectional survey of Australian general practitioners - Mariko Carey; Alison Zucca; Joel Rhee; Rob Sanson‐Fisher; Grace Norton; Christopher Oldmeadow; Tiffany Evans; Kichu Nair (Elsevier, 2021)
Abstract Objective: To examine general practitioners' views about how health assessments for older people should be conducted. Methods: General practitioners were randomly sampled from a national database of medical practitioners and invited to complete a survey. Survey items explored general practitioners' views about essential components of a 75+ Health Assessment and who should assess each component, consultation time, use of standardised templates and tools, and home visits. Results: Overall, 185 (19.2%) general practitioners participated. Of 61 items presented, 24 were rated 'essential' by ≥70% of practitioners, with an average estimated consultation time of 65 minutes. Of the 24 essential items, it was perceived that 21 could be assessed by either a general practitioner or clinic nurse. Most practitioners indicated a standardised template (86%) and standardised tools for complex issues (79%) should be used, and home visits conducted (75%). Conclusions: General practitioners agreed on 24 items as essential for every health assessment, with assessments estimated to take more than one hour. Implications for public health: Increases to remuneration for prolonged assessments or mechanisms for improving efficiency and quality of assessments are needed. Acceptable mechanisms may include standardised patient‐reported tools, standardised templates and the use of non‐medical staff to assist with assessments.